Pengaruh Gaji, Kompetensi dan Disiplin Kerja terhadap Produktivitas pada Karyawan Bhumimi Kebaya di Denpasar (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
There are a parcel of kebaya boutiques that we will discover these days, the progressively furious competition makes business people need to move forward and proceed to protect conventional territorial clothing in Bali, one of which is the Balinese kebaya. It's not as it were individuals in Bali who wear the Balinese kebaya. Numerous sightseers who excursion in Bali need to undertake wearing these conventional dress. What is the detailing of the issue and destinations of this inquire about and to decide the impact of compensation, competency and work teach on worker efficiency. The inquire about area was Bhumimi Kebaya workers and the test utilized was 40 respondents. The information examination strategies utilized are Legitimacy Test, Unwavering quality, Classical Suspicions, Different Direct Relapse, Coefficient of Assurance, T Test and F Test. Based on the investigate comes about it can be seen that compensation incorporates a critical positive impact on worker efficiency, competency encompasses a noteworthy positive impact on worker efficiency, teach work includes a critical positive impact on worker efficiency and at the same time compensation, competency and work teach have a noteworthy impact on worker efficiency. The size of the impact of the free factors on worker efficiency is 70.4%.